Bahasa Inggris - Raja Rahima Munawarah Raja Ahmad; Suhertina Suhertina; Hasbullah Hasbullah; Hasgimianti Hasgimianti; Yunita Efendi (MUWAZAH : jurnal kajian gender, 2023)
The spread of LGBT is increasingly widespread on social media through various content. One content that is similar to transgender behavior is imitation content which is very popular with teenagers. This article aims to describe the perceptions of Muslim teenagers who follow gender-similar content about waria, including behavior about being waria, identity and gender roles. Informants are teenagers aged 13-18 years with the criteria of being Muslim, who have followed social media accounts that carry out gender impersonation and show active liking, sharing or commenting activities, and have followed gender impersonation accounts for at least 1 year. There were 15 informants. This research was analyzed using the Colaizi 1978 model, namely reading data repeatedly, extracting significant statements in each answer description, coding meaningful and important statements, including them in themes, describing in detail and unambiguously, identifying similarities in points of view and sublimation thematic concept, finally validating the participants. The research results have shown that informants have different perceptions regarding the behavior of being a trans woman, namely positive and negative. Positive perceptions are influenced by cultural education in each individual. Negative perceptions are influenced by religious beliefs (beliefs). Negative perceptions of transgender identities are born from religious beliefs. Positive perceptions are born from social construction. Perceptions regarding the identity of trans women are divided into perceptions originating from knowledge about the human body which tend to be negative, and perceptions originating from social construction which tend to be positive.